Aplikasi Filter Digital untuk Citra Mengandung Derau Salt and Pepper Menggunakan Metode Directional Weighted Minimum Deviation - Rifa Hanifatunnisa; Rahmawati Hasanah (Jurnal Teknik: Media Pengembangan Ilmu dan Aplikasi Teknik, 2021)
Telecommunications technology growing rapidly, from the initial communication using letters, and now has reached the stage of image and video communication. In the process of transmitting data, both sound and images cannot be separated from noise. One solution to answer these problems is develop Digital Filter technology. In this research, a digital filter realized with an image object using the DWMD Filter method by detecting the type of salt and pepper noise. The DWMD Filter is a direction and standard deviation based digital data processing that improves the Median filter. With the PSNR, it is known that DWMD can produce better images than the Median Filter. This DWMD Filter method is coupled with an automatic Threshold determination to help the filter process to be faster where the largest PSNR difference is taken. The experimental results show that at a noise level of 5% - 65% the DWMD method produces a PSNR of 21-36 dB compared to the Median Filter of 13-29 dB. This research has an output in the form a desktop application that is equipped with features that can add salt and pepper noise in various densities and access images that can be converted into grayscale format.